Genesis of Understanding Internet Texts by Ukrainian Adolescents Depending on Their Internet Using Experience - Nataliia Akimova (East European Journal of Psycholinguistics, 2021)
The article presents the results of studying the genesis of the Internet text understanding by young readers depending on the level of their Internet user experience. The investigation reveals the regularities of the dynamics of successful understanding with the growth of the level of the Internet user experience at each stage of the comprehension process. For this purpose, the following methods were used: theoretical (deduction, induction, analysis, synthesis, generalization, systematization), empirical (experiment, method of semantic and pragmatic interpretations, content analysis, subjective scaling), and statistical (primary statistics, correlation analysis). The sample of the experiment consisted of 122 Ukrainian undergraduate students, including 14.8% men and 85.2% women. The study was conducted according to the author's methods "Success of understanding the texts of the Internet" and "Experience and focus of the Internet user". The understanding of Internet texts by adolescents is characterized by the activity of reception (indicating their significant interest in cyberspace), superficial assessment of the text complexity, and the tendency to predict the content by title and illustration. Meanwhile, it represents that the quality of rational and emotional text interpretation is quite low. Young people interpret only a quarter of the content of the message since their emotional understanding is usually inconsistent. However, a rational assessment is more accurate than an emotional one at this age. It is concluded that adolescents' genesis of Internet text understanding depends on their Internet user experience. Under the influence of the Internet user experience, the activity of the reception, the accuracy of expectations according to the illustration, and the consistency of emotional attitudes increase. However, the accumulation of experience sometimes has a negative effect on the dynamics of understanding, in particular on the interpretation of Internet news texts that seem unreasonably simple to young users. It is also recorded that at the stage of emotional identification, the rational evaluation of Internet texts with the accumulation of experience deteriorates. This feature is determined by the effect of unjustified confidence of Internet users.